2002
DOI: 10.1093/protein/15.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of proteasome cleavage motifs by neural networks

Abstract: We present a predictive method that can simulate an essential step in the antigen presentation in higher vertebrates, namely the step involving the proteasomal degradation of polypeptides into fragments which have the potential to bind to MHC Class I molecules. Proteasomal cleavage prediction algorithms published so far were trained on data from in vitro digestion experiments with constitutive proteasomes. As a result, they did not take into account the characteristics of the structurally modified proteasomes-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
234
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 268 publications
(243 citation statements)
references
References 53 publications
3
234
0
1
Order By: Relevance
“…NetChop Cterm has been trained on natural MHC class I ligands, whereas NetChop 20S is trained on in vitro cleavage data. It has previously been shown that NetChop 20S is less accurate in predicting the C-terminal ends of naturally occurring MHC class I ligands than NetChop C-term 2.0 [17]. Similar results were obtained in a new implementation of NetChop (NetChop C-term 3.0 and NetChop 20S-3.0), where a superior performance was obtained using a novel network training strategy and sequence encoding scheme [18].…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…NetChop Cterm has been trained on natural MHC class I ligands, whereas NetChop 20S is trained on in vitro cleavage data. It has previously been shown that NetChop 20S is less accurate in predicting the C-terminal ends of naturally occurring MHC class I ligands than NetChop C-term 2.0 [17]. Similar results were obtained in a new implementation of NetChop (NetChop C-term 3.0 and NetChop 20S-3.0), where a superior performance was obtained using a novel network training strategy and sequence encoding scheme [18].…”
Section: Introductionsupporting
confidence: 69%
“…On a very small dataset of only five epitopes from HIV Nef, Kesmir et al [17] showed that combining predictions of proteasomal cleavage with measured TAP and MHC class I binding affinity correlates well with the observed number of MHC class I ligands presented on the cell. In another study, Peters et al [16] improved identification of epitopes by combining predictions of binding affinities to the HLA-A*0201 allele with predictions of TAP transport efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations